An Investigation of Finite Element Models of Roller Bearings - Rahani, Ramin (My University, 2021)
Increasing demands on the design of transmissions for heavy trucks include higher loads, longer lifetime and reduction of noise. To design gearboxes with aid of the finite element method it is important to obtain precise force transfer and thus accurate stress distribution close to a roller bearing seat. Therefore, stable and numerically accurate bearing models are necessary. The purpose of the thesis is to accurately describe the local or average behavior of roller bearings and to present finite element results of the required detail level close to the bearings. It entails calibration of bearing models with results from commercial bearing analysis tools. The objectives are to find improved ways to model the change from contact to play between the rollers and the rings, study stiffness of different bearing distribution models, investigate mesh-sensitivity and implement axial stiffness in the bearing models. The Abaqus finite element software is used to predict the behavior of roller bearings. The analysis includes modelling of bearings and execution of load steps. Matlab scripts are used to post-process the bearing models and evaluate them with bearing analysis tools. The commercial software Shaft and Bearing Analysis (SABR) is used to create bearing reference models. An optimization process is implemented with Matlab to automate the convergence process of SABR. The developed model with GAP-elements agrees with the reference model in the same way as the model using nonlinear springs. Bearing models with different distribution loads show increasing deformation as the ring thickness increases. For bearings of extreme sizes, it is found that small rollers are slightly more flexible and large rollers a bit stiffer. The mesh study demonstrates that the relative size difference between adjacent elements does not affect the stiffness. When the spring spacing is equal to or smaller than the element size, the bearing stiffness is not affected by the spring spacing or the element size. The deflection of the bearings is influenced by the axial play. Axial stiffness should be high and does not give a large contribution to the total deflection. The results from the Abaqus bearing models provide good accuracy to model pure radial, pure axial and a combination of radial and axial loads along with bearing misalignments.
Keywords: Axial; Radial; Rings; Roller bearing; Springs; Stiffness